UPAYA HUKUM PEMBATALAN PUTUSAN ARBITRASE DI PENGADILAN - Pieter Radjawane (SASI, 2016)
In today's borderless business era, arbitration is a very popular dispute settlementinstitution used by businesses. However, it is not uncommon for business people, especiallythose who win cases, to be frustrated when faced with the implementation of arbitrationrulings involving the courts. The process of dispute resolution at the National ArbitrationInstitute, as it is commonly known in the Court, dispute resolution will lead to a decision(National Arbitration Award). Article 70 of Law no. 30 of 1999 on Arbitration and AlternativeDispute Settlement, affirming that the arbitral award can only be canceled if it is suspected tocontain elements of fake Letter / Document, or found documents hidden by the opponent or ajudgment taken from the guile by one of the parties in Examination, but the fact in practice thecourt still receives the request and cancels the arbitration decision outside the context of thatarticle which is the basis of the reference for the cancellation of the arbitral award.